Object Oriented Programming Untuk Sistem Informasi Pencatatan Hutang Dalam Pengadaan Obat Pada Rsud X - Indra Ava Dianta; Bagus Sudirman; Ahmad Ashifuddin Aqham (Jurnal Manajemen Informatika & Teknologi, 2021)
In the process of procuring this drug, there has been no special record of debt by the Pharmacy or the Finance Sector. The recording that was tried was only in the form of payment receipts from the Finance Sector to pay invoices from the drug industry that had supplied drugs to the Pharmacy Section. So that the Finance Sector has difficulty in managing debt and in recognizing the amount of debt and the maturity of debt payments for each supplier. With these obstacles, the Hospital requires an Information System for Recording Debts in the Procurement of Drugs to assist the Pharmaceutical and Financial Sector in recording debts, especially in the procurement of drugs. This data system uses an object-oriented programming language with SQL Server database to create an information system that can speed up the forest recording process in drug procurement